2016
DOI: 10.3389/fmicb.2016.00903
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Assessment of Bacterial Abundance in Soils, Sediments and Sludge

Abstract: Bacterial abundance is a fundamental measure in microbiology, but its assessment is often tedious, especially for soil, and sediment samples. To overcome this limitation, we adopted a time-efficient flow-cytometric (FCM) counting method involving cell detachment and separation from matrix particles by centrifugation in tubes receiving sample suspensions and Histodenz® solution. We used this approach to assess bacterial abundances in diverse soils (natural and agricultural), sediments (streams and lakes) and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 53 publications
(62 reference statements)
3
76
1
Order By: Relevance
“…This method constitutes a considerable improvement on previously developed protocols for biomass quantification on sand samples from water biofilters (MagicKnezev and van der Kooij, 2004). The protocol developed allows direct cell quantification free from potential biases introduced by assumptions such as equal average ATP content per cell (Frossard et al, 2016) and overcomes the limitations associated with qPCR quantification methods such as DNA extraction efficiency and yield (Bremen et al, 1999;Feinstein et al, 2009), and primer specificity. We optimised cell detachment for FCM quantification using a combination of chemical surfactants and ionic dispersants, together with low and high-energy sonication as a mechanical pretreatment, and different fixative methods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This method constitutes a considerable improvement on previously developed protocols for biomass quantification on sand samples from water biofilters (MagicKnezev and van der Kooij, 2004). The protocol developed allows direct cell quantification free from potential biases introduced by assumptions such as equal average ATP content per cell (Frossard et al, 2016) and overcomes the limitations associated with qPCR quantification methods such as DNA extraction efficiency and yield (Bremen et al, 1999;Feinstein et al, 2009), and primer specificity. We optimised cell detachment for FCM quantification using a combination of chemical surfactants and ionic dispersants, together with low and high-energy sonication as a mechanical pretreatment, and different fixative methods.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study, carried out on samples collected from several environments (sediments, soils, and sludge), directly compared cell abundances measured via the ATP assay and FCM on suspensions obtained after cell detachment via three cycles of sonication in a fixative solution (Frossard et al, 2016). The study showed that estimates based on the ATP assay yielded significantly higher average microbial abundances than the FCM method; the slope of the correlation between FCM and ATP was on average 0.36.…”
Section: Cross-comparison With Other Methodsmentioning
confidence: 96%
“…We believe the practicability and accessibility of many previously proposed solutions represent obstacles for the wider adaptation of quantitative microbiome profiling in human microbiome research. In particular, the flow cytometry-based approach requires considerable expertise for reproducible results, considering flow cytometric enumeration of microbial cells was initially restricted to pure cultures (10) and still remains challenging when performed in complex matrices (11).…”
Section: Main Textmentioning
confidence: 99%
“…Microbial biomass measurements are often influenced by microbial composition. Techniques used to measure microbial biomass abundance include phospholipid fatty acids (PFLAs) [60], substrate induced respiration (SIR) with selective inhibition of bacteria or fungi [61], DNAbased approaches such as qPCR [62,63], growth-based measurements [64], and particle counts by flow cytometry [65,66]. These techniques are affected by species' characteristics [24,67].…”
Section: Relative Effects Of Biomass Versus Community Composition On mentioning
confidence: 99%